Satisfaction with the rural tourism product of Cyprus - Farmaki, Anna (My University, 2014)
Rural tourism is a favourable developmental strategy for several destinations, due to the economic and social benefits it can yield to rural communities. Despite its popularity, the development of rural tourism has not been without problems. The aim of this study is to provide evidence of demand-side perceptions of the rural tourism product of Cyprus. Specifically, tourist satisfaction is measured to gain understanding of the island's rural tourism product performance. A survey was conducted on rural tourists, measuring tourist satisfaction across a series of attributes and by tourist motivation. Findings reveal that tourist motives and demographic factors influence satisfaction; specifically, rural tourists are not necessarily motivated by the rural setting whereas satisfaction appears to be affected by site-specific attribute evaluations. The findings highlight the importance of segmentation in rural tourism and suggest the adoption of a more refined marketing strategy if rural tourism development is to become successful.
Keywords: Cyprus; Rural tourism; Tourism marketing; Tourism planning; Tourist motivations; Tourist satisfaction